An Investigation of the Extracellular Region of Dfi1 Protein in Candida albicans - Pugliese, Antonia. (Tufts University. Tisch Library., 2019)
Candida albicans is a polymorphic yeast which grows as a commensal organism in much of the population. While most carriage is asymptomatic, C. albicans also functions as an opportunistic pathogen in immunocompromised patients, contributing to painful mucosal infections as well as life-threatening candidemia. This transition in lifestyle of the yeast is linked to a morphological transition to growth in the filamentous form. One factor that can influence the transition to filamentous growth, and which is related to pathogenicity in mice, is the Dfi1-dependent sensing of growth in contact with a surface. The Dfi1 protein is structured with two trans-membrane regions, with an extracellular region in between, and the C-terminal and N-terminal tails facing into the cell. The C-terminal tail is known to interact with calmodulin, and to be necessary to set off a kinase cascade in response to growth in contact with agar which includes the activation by phosphorylation of the MAP kinase Cek1. The extracellular region contains a section rich in serine and threonine residues, and Dfi1 is known to be heavily glycosylated with N- and O-linked glycosylations. The extracellular region also contains a highly conserved region, with high sequence homology to Dfi1-homologues in related Candida species. The importance of these extracellular regions was interrogated using four deletion mutants that lacked between 36-66 amino acids from the Dfi1 protein. The results of this project show that the highly conserved region of this domain is involved in Dfi1-dependent filamentation, as well as activation of Cek1 in response to Caspofungin and subsequent resistance to low levels of the anti-fungal drug. The serine threonine rich region of this domain is important for filamentation, but does not contribute to resistance to Caspofungin.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Molecular Microbiology.; Advisor: Carol Kumamoto.; Committee: Andrew Camilli, Joan Mecsas, Abraham Sonnenshein, and Wai-Leung Ng.; Keyword: Molecular biology.